Pre-Existing Frailty is Unrelated to Progression of Diffuse Subcortical Damage of Vascular Origin: A Longitudinal Prospective Study in Community-Dwelling Older Adults - Oscar H. Del Brutto; Bettsy Y. Recalde; Denisse A. Rumbea; Robertino M. Mera (SAGE Publishing, 2022)
Background: Both frailty and white matter hyperintensities (WMH) of presumed vascular origin are associated with enhanced expression of inflammatory biomarkers. Therefore, it is possible that pre-existing frailty predisposes to WMH progression. However, this relationship has not been explored. This population-based longitudinal prospective study aimed to assess the impact of frailty on subsequent progression of WMH in community-dwelling older adults living in rural Ecuador. Methods: Participants of the Atahualpa Project Cohort received baseline frailty assessment and brain MRIs. Frailty was evaluated by means of the Edmonton Frail Scale (EFS). WMH were graded according to the modified Fazekas scale. Individuals who received a follow-up brain MRI were included. Poisson regression models were fitted to assess the differential rate of WMH progression according to EFS score, after adjusting for demographics, level of education, and cardiovascular risk factors. Results: The study included 263 individuals aged ≥60 years (mean age: 65.7 ± 6.2 years; 57% women). The mean EFS score at baseline was 4 ± 2.3 points. Follow-up MRIs after a median follow-up of 6.5 years showed WMH progression in 103 (39%) individuals. The EFS score at baseline was associated with WMH progression in unadjusted analysis ( P  = .006). However, significance was not achieved in a multivariate Poisson regression model adjusted for relevant covariates (IRR: 1.07; 95% C.I.: 0.97-1.18; P  = .192). Conclusions: Study results do not support an independent relationship between frailty and WMH progression, adjusting for the confounding effect of aging.